A cognitive semantic study of biblical Hebrew: the root šlm for completeness-balance - Leong, Andrew Chin Hei (Brill, 2021)
"Semantic studies of the Biblical Hebrew verb "whole" have been influenced by those of its most invoked nominal form "whole". In this volume Andrew Chin Hei Leong shows that the concepts of balance, alliance, and completeness form the basic semantic structure of "whole". Previous studies on "whole" employed either historical or textual methodology, which has been dominant in biblical lexical studies. In addition to these methods, in Leong develops a systematic semantic methodology from Cognitive Semantics and Frame Semantics, to demonstrate that it is balance, rather than completeness, that is the most central concept in holding the semantic network together"–
Keywords: Bible; Hebrew language; Language; style; Semantics; Shlm (The Hebrew root)

How Many Books Are There in the Bible? (Part 1) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)
Author Note: There is a typo in the title of the publication. It was published “上” but it should be “下” instead.

How Many Books Are There in the Bible? (Part 2) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)

How Many Books Are There in the Bible? (Part 3) [In Traditional Chinese] - Leong, Andrew Chin Hei (St. Lazarus Parish Newsletter (New Series), 2021)

What Goes Around Comes Around? The (Non-)Existence of (Divine) Retribution in Ancient Chinese Literature and the Hebrew Bible - Leong, Andrew Chin Hei (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Does Romans 2:14 Refer to the Natural Law? - Leong, Chi Hei (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
Whilst after decades of research, exegetes have all agree on the complexity of Paul’s line of thinking in Rom 2:14–16, the ITC in its 2009 document, In Search of a Universal Ethic, still in an oversimplified manner propagates the view that Rom 2:14 presupposes a theory/theology of the natural law. This article makes plain the major disagreements among Pauline exegetes whether such presupposition stands by reviewing some major contributions to the discussion by raising major questions regarding the issue of φύσει in those verses, the nature of the law mentioned by Paul, the identity of the people Paul calls “Gentiles.” This article offers a more nuanced understanding of Rom 2:14. Keywords: Rom 2:14, ITC, Universal Ethic, Natural Law, φύσει, Gentiles
Number: 6